Diagnostic Value of Subjective Memory Complaints Assessed with a Single Item in Dominantly Inherited Alzheimer's Disease: Results of the DIAN Study. (2nd April 2015) - Laske, Christoph; Sohrabi, Hamid R.; Jasielec, Mateusz S.; Müller, Stephan; Koehler, Niklas K.; Gräber, Susanne; Förster, Stefan; Drzezga, Alexander; Mueller-Sarnowski, Felix; Danek, Adrian; Jucker, Mathias; Bateman, Randall J.; et al.
Abstract : Objective . We examined the diagnostic value of subjective memory complaints (SMCs) assessed with a single item in a large cross-sectional cohort consisting of families with autosomal dominant Alzheimer's disease (ADAD) participating in the Dominantly Inherited Alzheimer Network (DIAN). Methods . The baseline sample of 183 mutation carriers (MCs) and 117 noncarriers (NCs) was divided according to Clinical Dementia Rating (CDR) scale into preclinical (CDR 0; MCs: n = 107 ; NCs: n = 109 ), early symptomatic (CDR 0.5; MCs: n = 48 ; NCs: n = 8 ), and dementia stage (CDR ≥ 1; MCs: n = 28 ; NCs: n = 0 ). These groups were subdivided by the presence or absence of SMCs. Results . At CDR 0, SMCs were present in 12.1% of MCs and 9.2% of NCs ( P = 0.6 ) . At CDR 0.5, SMCs were present in 66.7% of MCs and 62.5% of NCs ( P = 1.0 ) . At CDR ≥ 1, SMCs were present in 96.4% of MCs. SMCs in MCs were significantly associated with CDR, logical memory scores, Geriatric Depression Scale, education, and estimated years to onset. Conclusions . The present study shows that SMCs assessed by a single-item scale have no diagnostic value to identify preclinical ADAD in asymptomatic individuals. These results demonstrate the need of further improvement of SMC measures that should be examined in large clinical trials.